Immunogenicity and safety of the adjuvanted recombinant zoster vaccine co-administered with the 23-valent pneumococcal polysaccharide vaccine in adults ≥50 years of age: A randomized trial. Issue 29 (5th July 2018) - Maréchal, Céline; Lal, Himal; Poder, Airi; Ferguson, Murdo; Enweonye, Igwebuike; Heineman, Thomas C; Hervé, Caroline; Rheault, Paul; Talli, Jaak; Wauters, Dominique; Oostvogels, Lidia
Highlights: Reactivation of latent varicella-zoster virus causes herpes zoster (HZ). The adjuvanted recombinant zoster vaccine (RZV) is >90% efficacious against HZ in adults aged ≥50 years. Immunogenicity and safety of RZV and PPSV23 were assessed when administered concomitantly or sequentially. No immunologic interference was observed between RZV and PPSV23 when co-administered. No safety concerns were identified during the study. Abstract: Background: This study evaluated immunogenicity and safety of the adjuvanted recombinant zoster vaccine (RZV) when the first dose was co-administered with the 23-valent pneumococcal polysaccharide vaccine (PPSV23) in adults aged ≥50 years. Methods: In this open label, multi-center study (NCT02045836), participants were randomized 1:1 to receive either the first dose of RZV and PPSV23, co-administered at Day 0 and the second dose of RZV at Month 2 (Co-Ad group), or PPSV23 at Day 0, the first dose of RZV at Month 2 and second dose of RZV at Month 4 (Control group). Co-primary objectives were the RZV vaccine response rate (VRR) in the Co-Ad group and the non-inferiority of the antibody responses to RZV and PPSV23 in the Co-Ad group compared to the Control group. Reactogenicity and safety were also assessed. Results: 865 participants were vaccinated (Co-Ad: 432, Control: 433). VRRs to RZV were >98% in both groups. Humoral immune responses to co-administration of RZV and PPSV23 were non-inferior to sequential administration. All three co-primary immunogenicity objectives were met. Solicited local symptoms after the first RZV dose were reported by similar percentages of participants in both groups. Solicited general symptoms were more frequently reported when the first dose of RZV and PPSV23 were co-administered. No differences were apparent between groups after the second RZV dose. Conclusions: No immunologic interference was observed between RZV and PPSV23 when co-administered in adults ≥50 years. No safety concerns were raised.